Recent Developments in the Theory of Foreign Exchange: Some Implications for Exchange Rate Policy - Douglas D. Purvis (Queen's University, Department of Economics, 1973)
As the title suggests, the purpose of this paper is to present a broad survey of recent theoretical developments relating to exchange rate management and exchange rate systems, and to suggest some possible implications for the formulation of exchange rate policy.
Keywords: 330